Optimizing Healthcare Through Digital Health and Wellness Solutions to Meet the Needs of Patients With Chronic Disease During the COVID-19 Era - Seixas, Azizi A.; Olaye, Iredia M.; Wall, Stephen P.; Dunn, Pat (Frontiers in Public Health, 2021)
COVID-19 disrupted and perturbed the status quo of chronic disease management in harmful and constructive ways. The pandemic exposed longstanding inefficiencies and deficiencies in chronic disease management and treatment in the United States, such as fragmented care, narrowly focused services, limited resources beyond office visits, expensive yet low-quality care, and inadequate access prevention and non-pharmacological resources. Additionally, COVID-19 survivors will add considerably more volume to and pressure on an already precarious system that struggles to meet the needs of patients with a chronic disease. Despite these harmful disruptions and perturbations, the pandemic catalyzed and normalized the use of telemedicine/telehealth in chronic disease management. However, the implementation and execution of telemedicine/telehealth are unfortunately relegated to the transportation of the office visit to a virtual interface which does not solve the inefficiencies above and deficiencies in chronic disease management. Although digital health technologies provide healthy lifestyle support and solutions to optimize adherence to treatment between visits can complement our health care system's contemporaneous modification, early evidence suggests they are underutilized, have poor engagement and retention. We argue the importance of reimagining chronic disease management and describe the scope and services needed to meet the challenges of the present, and future, a post-COVID era. Specifically, we describe how gamification of digital health solutions, primarily through a pantheoretical framework—one that uses personalized, contextualized, and behavioral science algorithms, data, and theory to ground treatments—can improve utilization and adherence to digital health solutions, treatments, and self-management behaviors of chronic diseases in and beyond the COVID-19 era.